1981
DOI: 10.1111/j.2042-7158.1981.tb13846.x
|View full text |Cite
|
Sign up to set email alerts
|

The influence of initial packing on the compression of powders

Abstract: The influence of the initial packing density on the compression properties of lactose and sodium chloride has been studied. Differences in initial packing density are eliminated for both materials at relatively low pressures. The results have been analysed by the equations of Kawakita (1956), Heckel (1961), and Cooper & Eaton (1962). The constants derived from the Cooper & Eaton equation are dependent on the choice of low pressure data. The Kawakita constants are influenced by the initial packing of the powder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1985
1985
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…A list of 209 immune genes putatively involved in honey bee defence against viruses 14 , 17 , 54 , 55 and Nosema spp. infections 30 , 33 , 38 , 45 , 56 was compiled from the literature (Supplementary Table S1 ).…”
Section: Methodsmentioning
confidence: 99%
“…A list of 209 immune genes putatively involved in honey bee defence against viruses 14 , 17 , 54 , 55 and Nosema spp. infections 30 , 33 , 38 , 45 , 56 was compiled from the literature (Supplementary Table S1 ).…”
Section: Methodsmentioning
confidence: 99%
“…For this purpose, flat-face punch of 12 mm diameter and hydraulic press were used. Equal volumes of powders (1357.17 mm 3 ) were compressed at 767.0, 1150.5, 1535.0, 1917.0, 2301.5 and 3068.1 kgf/cm 2 (5)(6)(7)(8)(9). Reaching the desired pressure it was kept at the required value for 30 sec (10).…”
Section: Determination Of the Compressibility Of Powdersmentioning
confidence: 99%
“…is: The Kawakita eq. is: In the Kawakita eq., "a" is a numeric parameter indicating the initial porosity of the compressed powder mass and "b" is the compression coefficient (7). At the dilutions that were prepared with Elcema G 250, the reason why the initial and the highest dilution values' consolidation differences were too similar to each other was that the particle size of Elcema G 250 and Lactose EP D-30 was not close to each other.…”
Section: Determination Of the Compressibility Of Powdersmentioning
confidence: 99%
“…In general, CBD measurements are based on uniaxially compressing a powder sample and measuring its density under a defined pressure. A number of studies involving low-pressure compression of pharmaceutical powders have been reported (Faulhammer et al, 2014;Heda et al, 1999;Kostelnik et al, 1968;Llusa et al, 2014;Nikolakakis et al, 1998;Podczeck and Lee-Amies, 1996;Sheikh-Salem and Fell, 1981;Sørensen et al, 2005Sørensen et al, , 2006. A previous report has also used a commercial compression instrument that can accommodate milligram powder quantities for bulk density measurements (Sørensen et al, 2005).…”
Section: Introductionmentioning
confidence: 99%